2012
DOI: 10.2169/internalmedicine.51.7329
|View full text |Cite
|
Sign up to set email alerts
|

Rescue Therapy for Lamivudine-resistant Chronic Hepatitis B: Adefovir Monotherapy, Adefovir Plus Lamivudine or Entecavir Combination Therapy

Abstract: Objective We aimed to compare the cumulative efficacy and resistance of ADV monotherapy, ADV add-on LAM (ADV + LAM), ADV and ETV (ADV + ETV) combination therapy in LAM-resistant patients. Methods Ninety-one adult CHB patients with LAM-resistance mutations (YMDD) were identified. Of these 91, 29 patients were treated with ADV monotherapy, 30 were treated with ADV + LAM and 32 were treated with ADV + ETV combination therapy, for at least 24 months. Results The mean serum HBV-DNA decreases from baseline at 3, 6, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 35 publications
1
23
1
Order By: Relevance
“…And this superiority of ETV + ADV could be explained by the effect of ETV against ADV resistant mutation and the effect of ADV against LAM resistant mutation. In present study, we also found that ETV + ADV combination therapy showed ideal efficacy in HBV DNA suppression over 24 months in patients after LAM and ADV therapy failures, and this finding also supported the superior efficacy of ETV + ADV combination therapy in a certain degree [19]. …”
Section: Discussionsupporting
confidence: 81%
“…And this superiority of ETV + ADV could be explained by the effect of ETV against ADV resistant mutation and the effect of ADV against LAM resistant mutation. In present study, we also found that ETV + ADV combination therapy showed ideal efficacy in HBV DNA suppression over 24 months in patients after LAM and ADV therapy failures, and this finding also supported the superior efficacy of ETV + ADV combination therapy in a certain degree [19]. …”
Section: Discussionsupporting
confidence: 81%
“…By adhering to the inclusion criteria, 24 of those studies were excluded. Finally, 4 studies were chosen for inclusion in the meta‐analysis, which comprised a total of 323 patients (Figure S1).…”
Section: Resultsmentioning
confidence: 99%
“…The characteristics of the included studies including population size, age, rate of HBeAg positivity, serum alanine aminotransferase (ALT), serum HBV DNA levels and variants are summarized in Table . The study population was Asian for all four studies, with two studies composed of Chinese and two composed of Korea subjects. Two studies were randomized controlled trials and two were cohorts.…”
Section: Resultsmentioning
confidence: 99%
“…In both groups, the proportions of patients with HBV‐DNA < 60 IU/mL increased gradually and were comparable at week 104 (42.2% and 34.1%, respectively), with decreased levels of resistance mutants selected during second‐ or third‐line therapy, and no emergence for additional multidrug resistance mutants . In another study in LAM‐resistant patients, ADV + ETV demonstrated faster and significantly greater virologic suppression after 24 months than switch to ADV monotherapy or ADV add‐on therapy . Another small study assessed ETV + ADV as third‐line therapy after failure on initial LAM and any of the second‐line options ETV, ADV, or LAM + ADV.…”
Section: Discussionmentioning
confidence: 99%